Silicon Application Enhances Sugarcane Growth by Impairing the Development of Larval Sugarcane Borer - Sousa, Amanda Cristina Guimarães [UNESP]; Pinto, Ciro Pedro Guidotti [UNESP]; dos Santos, Ana Letícia Zero [UNESP]; Fonseca, Sandy Sousa [UNESP]; Camargo, Mônica Sartori; Rossi, Guilherme Duarte [UNESP] (Springer Nature, 2024)
Sugarcane borer, Diatraea saccharalis, is one of the main insect pests of sugarcane fields, and it has been mainly managed by the use of chemical or biological controls. Considering the benefits of Silicon (Si) fertilization against pests, it was assessed the development of sugarcane borer larvae and sugarcane growth with and without Si. A greenhouse experiment was conducted using a factorial design (2 × 2) with 10 repetitions. Two commercial sugarcane varieties were evaluated: SP80-3280 and IAC91-1099, which have, respectively, susceptibility, and intermediate resistance to D. saccharalis. Si was applied in soil in an equivalent rate of 800 kg of Si ha−1. Before herbivory, Si increased stalk diameter and plant height in both varieties, and number of leaves and leaf width were only increased in IAC91-1099. After 20 days of herbivory, Si increased stalk diameter in both varieties and plant height in IAC91-1099, but decreased the number of leaves and leaf width in SP80-3280. Larval D. saccharalis showed a reduced weight and a greater index for mandible abrasion after feeding Si-treated plants independently of variety. No influence of Si-treated plants was found in immunological parameters of larvae (total number of hemocytes, cell viability, encapsulation capability, lysozyme active). The activity of phenol oxidase, an immunological and stress marker for insects, was greater in larval D. saccharalis fed with IAC 91-1099, independently of Si. In conclusion, Si application improved sugarcane growth of IAC91-1099 and impaired the development of larval D. saccharalis in both sugarcane varieties.
Keywords: Abiotic elicitor; Diatraea saccharalis; Plant resistance; Plant tolerance; Potassium silicate